An introduction to international relations - Devetak, Richard; Burke, Anthony 1966-; George, Jim 1946- (Cambridge University Press, 2017)
An Introduction to International Relations is a comprehensive introduction to the history, theories, developments and debates that shape the dynamic discipline of international relations and contemporary world politics. Bringing together an expert author team comprising leading academics from Australia and around the world, it allows readers to explore the discipline from both Australian and global perspectives. Known for its clear, easy-to-read style and relevant, real-world examples, the text has been fully updated and revised to reflect current research and the changing global political climate. This edition features extensive new material on: international history from World War I to World War II; international law; the globalisation of international society; and terrorism. A companion website for instructors offers additional case studies, critical thinking questions and links to relevant video and web materials that bring international relations theory to life." -- Provided by publisher